An Exploration of Consumers' Response to Online Service Recovery Initiatives. (2017) - Ozuem, Wilson; Patel, Amisha; Howell, Kerry E.; Lancaster, Geoff
The focus of this paper is on levels of service failure and recovery strategies in relation to UK online fashion retailers. In a changing social, political and economic environment the use of information technology has permeated all forms of organisations: from private to public, local to global, old and new. Parallel with this development, companies have developed and experimented with new means of interacting with customers, and have devised and applied a variety of marketing strategies. The deployment of the internet, along with its subsets, has created a number of new opportunities, as well as a range of uncertainties and burdens, particularly on consumer perceptions of service quality, service failure and recovery. This paper contributes to extant knowledge and offers an understanding of behavioural-related issues, e.g. understanding consumer behaviour in the development of innovative business models in the industry.